Phytase activity of lactic acid bacteria and their impact on the solubility of minerals from wholemeal wheat bread. (3rd October 2015) - Cizeikiene, Dalia; Juodeikiene, Grazina; Bartkiene, Elena; Damasius, Jonas; Paskevicius, Algimantas
Abstract: The objective of this study was to determinate phytase activity of bacteriocins producing lactic acid bacteria previously isolated from spontaneous rye sourdough. The results show that the highest extracellular phytase activity produces Pediococcus pentosaceus KTU05-8 and KTU05-9 strains with a volumetric phytase activity of 32 and 54 U/ml, respectively, under conditions similar to leavening of bread dough (pH 5.5 and 30 °C). In vitro studies in simulated gastrointestinal tract media pH provide that bioproducts prepared with P. pentosaceus strains used in wholemeal wheat bread preparation increase solubility of iron, zinc, manganese, calcium and phosphorus average 30%. Therefore, P. pentosaceus KTU05-9 and KTU05-8 strains could be recommended to use as a starter for sourdough preparation for increasing of mineral bioavailability from wholemeal wheat bread.